IMPROVEMENT OF PEDAGOGICAL COMPETENCE OF TEACHERS THROUGH THE METHOD OF MONITORING AND EVALUATION AT SDN SIDOTOPO WETAN I/255 SURABAYA ACADEMIC YEAR 2021/2022 - Mohammad Ismail (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
AbstractThe school principal has a very important role in a school. A good school is dependent to its school principal. If the principal is able to organize the whole components in the school to achieve the goals set in the beginning. The school principal must have a vision for the future and follow the changes that occur in the globalization era.In this action research, the monitoring and evaluation method is considered as the most appropriate one in applying managerial supervision to the school principal, compared to the other methods such as Focus Group Discussion (FGD), Workshop, and Delphi. As an advantage, researchers can directly monitor and contact with the conditions and developments in the field.The School Action Research (SAR) was conducted at SDN Sidotopo Wetan I/255 Surabaya. Research was scheduled from September 2021 to October 2021. The subject of research was the Teachers in SDN Sidotopo Wetan I/255 Surabaya. The number of Respondents were as many as 13 people.From the results, the implementation of a Method of Monitoring and Evaluation can Improve the pedagogical Competence of teachers at SDN Sidotopo Wetan I/255 Surabaya within Academic Year 2021/2022. The result of pedagogical competence improvement of teachers through the Method of Monitoring and Evaluation at SDN Sidotopo Wetan I/255 Surabaya Academic Year 2021/2022 is excellent. In cycle 2, the ability of teachers increased significantly compared to the earlier phase. In cycle 1, the average ability grew from 75 % to 86 % in cycle 2 after some improvement was being conducted in the cycle. Several weaknesses in cycle 1 included specifically aspect number 4 (the improvement activities for students); so, teachers were encouraged to conduct remedial activities for students with lower scores